2022
DOI: 10.3390/jmmp6040076
|View full text |Cite
|
Sign up to set email alerts
|

Flange Wrinkling in Deep-Drawing: Experiments, Simulations and a Reduced-Order Model

Abstract: Flange wrinkling is often seen in deep-drawing process when the applied blankholding force is too small. This paper investigates the plastic wrinkling of flange under a constant blankholding force. A series of deep-drawing experiments of AA1100-O blanks are conducted with different blankholding forces. The critical cup height and wrinkling wave numbers for each case is established. A reduced-order model of flange wrinkling is developed using the energy method, which is implemented to predict the flange wrinkli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
7
0
Order By: Relevance
“…In stamping processes, the use of an edge holder is imperative to prevent the flange edge from wrinkling. Additionally, the reliability of the simulation optimization results is verified by experiments, as shown in Figure 15 b. Chen et al [ 185 ] conducted experiments, simulations and reduced-order calculations on flange wrinkling in the deep drawing process of the AA1100 aluminum alloy. The flange wrinkle height and wrinkle numbers predicted by the FE model and reduced-order model are consistent with experimental results, as shown in Figure 15 c. Based on the established sheet deformation instability model, Wang et al [ 186 ] undertook the FE model to compare the prediction results of FLC, maximum stress and strain instability criteria; they found that a new FLC instability criterion can be more accurately predicted and verified for wrinkling.…”
Section: Analytical Methods Of Deformation Instabilitymentioning
confidence: 83%
See 1 more Smart Citation
“…In stamping processes, the use of an edge holder is imperative to prevent the flange edge from wrinkling. Additionally, the reliability of the simulation optimization results is verified by experiments, as shown in Figure 15 b. Chen et al [ 185 ] conducted experiments, simulations and reduced-order calculations on flange wrinkling in the deep drawing process of the AA1100 aluminum alloy. The flange wrinkle height and wrinkle numbers predicted by the FE model and reduced-order model are consistent with experimental results, as shown in Figure 15 c. Based on the established sheet deformation instability model, Wang et al [ 186 ] undertook the FE model to compare the prediction results of FLC, maximum stress and strain instability criteria; they found that a new FLC instability criterion can be more accurately predicted and verified for wrinkling.…”
Section: Analytical Methods Of Deformation Instabilitymentioning
confidence: 83%
“… Research results of deformation instability by finite element simulation and experimental methods: ( a ) flange forming of the spinning thin-walled plate [ 171 ]; ( b ) stamping forming of a titanium alloy mechanical handle [ 184 ]; ( c ) deep drawing of the AA1100 aluminum alloy [ 185 ]; ( d ) 304 steel plate shear wrinkling test [ 187 ]; ( e ) various buckling modes of tube compression instability [ 140 ]. …”
Section: Figurementioning
confidence: 99%
“…6) and then finding the corresponding punch displacement. Wrinkling is determined by simulating the blank with and without wrinkling imperfection and measuring the punch and blank holder displacements, as in our earlier work by Chen et al (1).…”
Section: Simulation Resultsmentioning
confidence: 99%
“…In the past, many investigations were conducted to identify influencing factors of the deep drawing process, e.g., friction, blank holder force, blank shape, and punch velocity [20]. Most of the work is aimed at producing a component that is free of defects at the macroscopic level for instance considering wrinkling [21,22], sheet thinning [23], and springback [24,25]. Besides that, efforts have been made to numerically predict damage occurrence during deep drawing.…”
Section: Damage Evolution During Deep Drawingmentioning
confidence: 99%